Performance Analysis of Solar Gain and Day lighting Effect Using Different Choices of Materials of Double-Skin Facade under Desert Climatic Conditions - Al Tekreeti, Samar Rafie Shaker (2015)
This study presents a performance analysis of solar gain and day lighting effect using different choices of materials of double-skin facade under desert climatic conditions. In addition, it evaluates the possible positive effects that the use of double skin facades can have on the indoor environment in commercial buildings such as offices. During the working process different literature sources and research about double skin facades and indoor environment conditions are gathered and analyzed. A computer simulation based research will be made in order to compare the theory and get a better insight of how these systems function in practice. Furthermore, literature is taken into consideration regarding double-skin facades, including its classification and its effectiveness and feasibility in hot and humid climates. The analysis led to many findings and to a section about outer skin materials and effective cavity depth reaching the aim for reduction in cooling load and maximizing daylight penetration at the same time. A computer simulation software investigation tools, conditions and parameters were set for appropriate grounds of the study. Simulation results were used in comparison with a baseline case and assimilated multiple system into the simulation software to better understand the effect on each selected material. Results show a range of reduction for each material profile starting from 10% and up to 37 % cooling load consumption savings utilizing double skin facade at the depth of 1.0 meter cavity with an open shaft configuration when using concrete and glass as external skin. The dissertation concludes with limitations and suggestions for future studies.